Ethiopia : Managing Water Resources to Maximize Sustainable Growth - World Bank (Washington, DC, 2012)
This report looks at, and beyond, the management hydrological variability to interventions aimed at decreasing the vulnerability of the economy to these shocks. It helps clarify linkages between the country's economic performance and its water resources endowment and management. It then uses this analysis to recommend both water resource strategies and economic and sectoral policies that will enhance growth and insulate the Ethiopian people and economy from the often devastating, economy-wide effects of water shocks. This report finds that unmitigated hydrological variability currently costs the economy over one third of its growth potential. The very structure of the Ethiopian economy with its heavy reliance on rainfed subsistence agriculture makes it particularly vulnerable to hydrological variability. Its current extremely low levels of hydraulic infrastructure and limited water resources management capacity undermine attempts to manage variability. These circumstances leave Ethiopia's economic performance virtually hostage to its hydrology.